Corona, the Lockdown, and the Media A Quantitative Frame Analysis of Media Coverage and Restrictive Policy Responses - Bernhagen, Patrick (De Gruyter, 2024)
Corona, the Lockdown, and the Media investigates media influence on policies to contain the COVID-19 pandemic. Bernhagen and Kybelka propose that news reporting on the pandemic pitches human impact against economic consequences of the virus and of restrictive policy measures designed to contain it. They argue that the use of these frames influences governments' decisions to enact or lift lockdown measures. Using time series data from England, France, and Germany, the authors show that news reporting on COVID-19 was indeed characterized by these media frames. However, there is no evidence of media influence on government policy. Instead, the authors find that anti-pandemic policy decisions were responsive to public opinion in these countries
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Jan 2024)
Keywords: COVID-19; Frame ‹Journalismus›; Krisenmanagement; Massenmedien / Wirkung; Staatstätigkeit; SOCIAL SCIENCE / Media Studies